Geographic associations between lactase phenotype, multiple sclerosis, and inflammatory bowel diseases; Does obesity trump geography?. (November 2016) - Szilagyi, Andew; Xue, Xiaoqing
Abstract: Geographic patterns with diminishing rates from north to south toward the equator have been described for a number of diseases, putatively related largely to "western" lifestyle. Among these the inflammatory bowel diseases; Crohn's (CD) and Ulcerative colitis (UC) have been prominent in sharing distributions with a number of autoimmune diseases. One of the interesting associations is the epidemiologic similarity with multiple sclerosis (MS). However, in addition, at least some of these diseases also correlated inversely with lactase non persistent population (LNP) distributions. It is hypothesized that MS should also have an inverse relationship with LNP. We provide support for this by comparing published MS, CD, UC and LNP national rates to the beginning of the new millennium. Possible links among these diseases may be an evolutionary signature of new genes which may have accompanied emergence of lactase persistence millennia ago. The emergent phenotypic dichotomy also forced different assimilation responses to lactose digestion. While intestinal retention of lactase results in direct host enzymatic digestion, in LNP persons intestinal bacterial metabolism of lactose impacts on the host micro-flora. These microbial changes may play some role in altering rates of diseases including IBD and MS. However, since the late 20th century previously observed patterns are changing. Although industrialization is considered to play an important modifying role, the rising rates of obesity with an emphasis on diet, and microfloral pathogenesis, but with an independent geographic pattern may also facilitate altering rates and geographic distributions of both of these and other diseases.